Composition: Music as inpiration and generator of space - Messaris, Anastasia Miranda (School of Architecture, Planning and Geomatics, 2017)
The analogy between the two arts of music and architecture has been a central theoretical theme since the conception of either. Emerging from a background that is situated in both architectural and musical instruction, the correlation between the two has always provided a certain degree of fascination for me. Having understood the linear narrative running between the translation of music and architecture, I endeavoured to locate a more conceptual foothold from which to derive my arguments. The essays below outline my discovery and development of the topic, transforming a simple analogy into a conceptual way of reading context so as to create an architectural composition of space, just as a musician uses the tools of notes (sounds), rests (silences), instrument quality, beat (time) and sequence to create a musical composition. This thesis developed similarly to that of a musical composition: where themes are presented, then developed, then treated in new ways, and finally returned to, creating a final composition that moves through exposition (stability), development (heightened tension and conflict) and resolution.